Evidence for merger-driven growth in luminous, high-z, obscured AGNs in the CANDELS/COSMOS field - Donley, J. L.; Kartaltepe, J.; Kocevski, D.; Salvato, M.; Santini, P.; Suh, H.; Civano, F.; Koekemoer, A.M.; Trump, J.; Brusa, M.; Cardamone, C.; Castro, A.; et al. (American Astronomical Society, 2018)
While major mergers have long been proposed as a driver of both active galactic nucleus (AGN) activity and the MBH–sbulge relation, studies of moderate to high-redshift Seyfert-luminosity AGN hosts have found little evidence for enhanced rates of interactions. However, both theory and observation suggest that while these AGNs may be fueled by stochastic accretion and secular processes, high-luminosity, high-redshift, and heavily obscured AGNs are the AGNs most likely to be merger-driven. To better sample this population of AGNs, we turn to infrared selection in the CANDELS/COSMOS field. Compared to their lower-luminosity and less obscured X-ray-only counterparts, IR-only AGNs (luminous, heavily obscured AGNs) are more likely to be classified as either irregular (50+ or - 12% versus 9 +5 % or -2%) or asymmetric (69 +9% or– 13 % versus 17 +6 % or -4%) and are less likely to have a spheroidal component (31 +13% or -9% versus 77+6% or -4%). Furthermore, IR-only AGNs are also significantly more likely than X-ray-only AGNs (75 +8% or -13% versus 31 + or – 6 %) to be classified either as interacting or merging in a way that significantly disturbs the host galaxy or as disturbed, though not clearly interacting or merging, which potentially represents the late stages of a major merger. This suggests that while major mergers may not contribute significantly to the fueling of Seyfert luminosity AGNs, interactions appear to play a more dominant role in the triggering and fueling of high-luminosity heavily obscured AGNs.